A siloxane nanocomposite material and its preparation method and application

By preparing silicone nanocomposites, the problems of damage and adhesion of temporal muscle after bone decompression surgery were solved, and the effects of antibacterial, anti-inflammatory and promoting temporal muscle repair were achieved, improving the quality of patients' prognosis and reducing medical costs.

CN119280473BActive Publication Date: 2025-04-22HARBIN MEDICAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411803692.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-22
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent or solve problems such as damage to the temporal muscle, adhesion formation and infection after decompression of the bone flap, resulting in increased postoperative complications, reduced prognosis quality and high medical costs.

Method used

Silicone nanocomposites were prepared by mixing nanosilver, quercetin and solvent evenly and reacting with polysiloxane films to prepare silicone nanocomposites with anti-adhesion, broad-spectrum antibacterial, anti-inflammatory and promoting temporal muscle repair.

Benefits of technology

This material can significantly reduce the occurrence of postoperative complications, improve the repair effect of the temporalis muscle, reduce the financial and mental burden of patients and families, and reduce medical costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280473B_ABST
    Figure CN119280473B_ABST
Patent Text Reader

Abstract

The present invention provides a siloxane nanocomposite material and its preparation method and application, belonging to the field of biochemical technology. The preparation method provided by the present invention is: after nano silver, quercetin and solvent are evenly mixed, a suspension is obtained; a polysiloxane film is added to the suspension for stirring reaction to obtain the siloxane nanocomposite material; the mass ratio of the nano silver and the polysiloxane film is 1:10-1:20; the mass volume ratio of the polysiloxane film to the solvent is 0.2-0.25g:30mL; the amount of quercetin added is 3mg / mL solvent. The preparation method provided by the present invention is simple, and the core components such as raw materials siloxane, nano silver, quercetin are easy to obtain, and the price is low, and the production cost is low. The prepared siloxane nanocomposite material has the advantages of good anti-adhesion, broad-spectrum antibacterial, anti-inflammatory and promoting the repair of temporal muscle after DC, which can improve the quality of patient prognosis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biochemistry, and in particular to a siloxane nanocomposite material and a preparation method and application thereof. Background Art

[0002] In the field of neurosurgery, when acute diseases of the central nervous system such as stroke and traumatic brain injury occur, they are usually accompanied by a sharp increase in intracranial pressure. High intracranial pressure can lead to ischemic necrosis of brain tissue and even brain herniation, endangering the patient's life. As a neurosurgical procedure involving the removal of part of the skull to accommodate brain swelling, decompressive craniectomy (DC) is usually accompanied by damage to the temporalis muscle and adhesions between the bone flap and the dura mater. This is a common but very difficult problem in clinical practice. It not only seriously increases the cost, difficulty and occurrence of postoperative complications of subsequent cranioplasty, such as causing inflammatory reactions, epilepsy, cerebrospinal fluid leakage, induced infection and life-threatening, but also seriously changes the patient's appearance and affects the normal functions of the temporalis muscle such as chewing, and even causes severe pain. These have greatly reduced the quality of the patient's prognosis and brought heavy mental and economic burdens to the patient and his family.

[0003] While this actual clinical phenomenon needs to be solved urgently, there are almost no materials on the market that can directly prevent or solve the above problems. The more common artificial dura mater materials in clinical practice, including tetrafluoroethylene artificial dura mater (PTFE) and acellular matrix dura mater patch (ADM), are very expensive, which makes patients discouraged, and may provide some characteristics that are not required for this application, such as affecting the sealing ability around the suture and the surface of tissue ingrowth; on the other hand, these materials are also prone to infection, inflammatory response and other unpredictable follow-up difficult problems when placed in the skull. Most importantly, these biological dura maters on the market cannot really effectively prevent infection, adhesion formation and promote the repair of the temporalis muscle. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a siloxane nanocomposite material and a preparation method and application thereof.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is a method for preparing a siloxane nanocomposite material, comprising: uniformly mixing nanosilver, quercetin and a solvent to obtain a suspension; adding a polysiloxane film to the suspension for stirring and reaction to obtain the siloxane nanocomposite material;

[0007] The mass ratio of the nanosilver to the polysiloxane film is 1:10-1:20; the mass volume ratio of the polysiloxane film to the solvent is 0.2-0.25 g:30 mL; and the added amount of the quercetin is 3 mg / mL of the solvent.

[0008] The second technical solution of the present invention is a siloxane nanocomposite material prepared by the above preparation method.

[0009] A third technical solution of the present invention is an application of the above-mentioned silicone nanocomposite material in the repair of the temporalis muscle after craniectomy for non-disease diagnosis and treatment purposes.

[0010] The present invention discloses the following technical effects:

[0011] The preparation method of the siloxane nanocomposite material provided by the invention is simple, the core components such as raw materials siloxane, nanosilver, quercetin, etc. are easy to obtain, and the price is low, so the production cost is low.

[0012] The siloxane nanocomposite material provided by the present invention has the advantages of good anti-adhesion, broad-spectrum antibacterial and anti-inflammatory properties and can promote the repair of the temporalis muscle after decompressive craniectomy (DC), can improve the quality of patient prognosis, and reduce the burden on families and society.

[0013] The siloxane nanocomposite material provided by the present invention has good sustained-release performance and can further improve the repair effect of the temporalis muscle after bone flap removal. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 is the chemical structural formula of the polysiloxane in the present invention;

[0016] Figure 2 A schematic diagram of the components of the AQS of the present invention and its application in an animal craniectomy model;

[0017] Figure 3 This is a scanning electron microscope photo of AQS in the effect verification example;

[0018] Figure 4 The 2D and 3D structures of polysiloxane and AQS under atomic force microscopy in the effect verification example, where A and B are the 2D and 3D morphologies of polysiloxane materials, respectively, and C and D are the 2D and 3D morphologies of AQS, respectively;

[0019] Figure 5The hydrophobic angles of tetrafluoroethylene material, siloxane nanocomposite AQS and original polysiloxane film in the effect verification example, wherein A is tetrafluoroethylene material, B is original polysiloxane film, and C is siloxane nanocomposite AQS;

[0020] Figure 6 This is an experiment to test the bactericidal ability of different materials against Escherichia coli and Staphylococcus aureus in the effect verification example;

[0021] Figure 7 The results of the slow release test of silver and quercetin in AQS in the effect verification example, where A is silver and B is quercetin;

[0022] Figure 8 These are immunofluorescence images of the expression levels of pro-inflammatory factor interleukin 6 (IL-6), anti-inflammatory factor 10 (IL-10) and proliferating cell nuclear antigen (PCNA) in the damaged temporalis muscle in the animal model in the effect verification example, where A and B are the interleukin 6 levels on the 7th and 14th days after rat modeling, C and D are the interleukin 10 levels on the 7th and 14th days after rat modeling, and E and F are the PCNA levels on the 7th and 14th days after rat modeling;

[0023] Fig. 9 To verify the effect of AQS on the temporalis muscle in a rat craniectomy model at 7 and 14 days after surgery. DETAILED DESCRIPTION

[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0029] The room temperature in the present invention is 15-35°C.

[0030] One of the technical solutions of the present invention is a method for preparing a siloxane nanocomposite material, comprising uniformly mixing nanosilver, quercetin and a solvent to obtain a suspension; adding a polysiloxane film to the suspension for stirring and reaction to obtain the siloxane nanocomposite material (AQS);

[0031] The mass ratio of the nanosilver to the polysiloxane film is 1:10-1:20; the mass volume ratio of the polysiloxane film to the solvent is 0.2-0.25 g:30 mL; and the added amount of the quercetin is 3 mg / mL of the solvent.

[0032] In the present invention, the preparation method of the polysiloxane film comes from "Preparation of Robust, Room-Temperature Self-Healable and Recyclable Polysiloxanes Based on Hierarchical Hard Domains, Pengyuan Lai. et al, Advanced Engineering Materials". The polysiloxane material actually used was donated by the author of the article.

[0033] In some embodiments of the present invention, the particle size of the nanosilver is 100 nm.

[0034] In some embodiments of the present invention, the solvent is deionized water; the parameters of the stirring reaction are: stirring in a closed environment at room temperature and pressure, away from light, for 12-24 hours; and the stirring speed is 400-500 rpm.

[0035] In some embodiments of the present invention, after the stirring reaction is completed, the step of drying the obtained product is also included; the drying is air-drying at room temperature away from light for 0.5 to 1 hour.

[0036] The invention loads nano silver and quercetin on a polysiloxane material through a stirring reaction, giving AQS a sustained-release performance. The loaded nano silver and quercetin enable the obtained siloxane nano composite material to have antibacterial and anti-inflammatory effects while greatly increasing the hydrophobicity of the polysiloxane material. The hydrophobicity is more conducive to preventing the temporalis muscle from forming adhesions with the bone flap and the dura mater, thereby promoting the healing of the temporalis muscle and reducing the occurrence of complications.

[0037] The second technical solution of the present invention is a siloxane nanocomposite material prepared by the above preparation method.

[0038] A third technical solution of the present invention is an application of the above-mentioned silicone nanocomposite material in the repair of the temporalis muscle after craniectomy for non-disease diagnosis and treatment purposes.

[0039] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0040] Unless otherwise specified, the raw materials and reagents used in the examples can be obtained through commercial channels.

[0041] The preparation method of polysiloxane in the embodiment comes from "Preparation of Robust, Room-Temperature Self-Healable and Recyclable Polysiloxanes Based on HierarchicalHard Domains, Pengyuan Lai. et al, Advanced Engineering Materials". The polysiloxane material actually used was donated by the author of the article. Specifically, the preparation method of polysiloxane is as follows: first, dissolve bis(3-aminopropyl)-terminated polydimethylsiloxane (APDMS, 3g, 10mmol) and 10ml of dry-treated tetrahydrofuran in a 50ml round-bottom flask. Dissolve 4,4'-diphenylmethane diisocyanate (MDI) and isophorone diisocyanate (IPDI) in tetrahydrofuran in a stoichiometric ratio [APDMS / MDI / IPDI / 2-aminophenylboronic acid = 1:0.6:1.4:2], and add the mixed solution dropwise to the above-mentioned APDMS solution. The reaction is carried out under nitrogen and ice-water bath conditions. After stirring for 5 hours, an APDMS-NCO solution was obtained and stored for later use. Subsequently, 2-aminophenylboronic acid (0.274 g, 20 mmol) was dissolved in 10 mL of tetrahydrofuran, the solution was stirred for 5 minutes, and a small amount of insoluble matter was removed with a microporous filter membrane. The solution was then added to the aforementioned APDMS-NCO solution and stirred for 5 hours to obtain an APDMS-MDI-IPDI-B solution. The solution was distilled under reduced pressure to remove excess tetrahydrofuran, poured into a Teflon mold, and dried continuously at room temperature for 24 hours to obtain an APDMS-MDI-IPDI-B film. Subsequently, drying was continued at room temperature in a vacuum oven for 12 hours to finally obtain polysiloxane, whose structure is as shown Figure 1 shown. Example 1

[0042] The preparation steps of siloxane nanocomposite (AQS) are as follows:

[0043] Weigh 0.2 grams of polysiloxane flakes with a precision balance of no less than milligram level for later use. Then add nanosilver powder with a particle size of about 100nm (the mass ratio of nanosilver addition to polysiloxane is 1:10) and quercetin (the amount of quercetin added is 3mg / mL deionized water) to 30ml deionized water, and use an ultrasonic machine to treat for 45 minutes to evenly disperse the nanosilver powder and quercetin in deionized water to obtain a suspension. Then, add the polysiloxane flakes prepared above to the suspension, put in a sterilized clean magnetic bar, and use a magnetic stirrer to stir in a closed manner at room temperature and pressure for 24 hours in a dark place at a speed of 400 rpm. Finally, take out the mixed flakes and air-dry them in a mold in a dark place at room temperature for 1 hour to obtain a siloxane nanocomposite material (AQS).

[0044] Effect verification example

[0045] The distribution of nanosilver on AQS is shown in Figure 2. Figure 3 As shown in Figure 2, the scanning electron microscopy results show that the nanosilver is evenly distributed on the surface of AQS without agglomeration, which is more conducive to the subsequent antibacterial properties of AQS. The nanosilver on AQS is spherical, and the average diameter of the nanosilver is about 100 nm according to the measurement.

[0046] The structure of AQS is as follows Figure 4 As shown, Figure 4 Middle A and Figure 4 B shows the 2D and 3D morphologies of polysiloxane materials observed under an atomic force microscope. Figure 4 Middle C and Figure 4 Middle D shows the 2D and 3D morphologies of AQS. Quercetin and silver nanoparticles are evenly distributed on AQS, which is consistent with the scanning electron microscopy. Figure 4 The spherical objects in C are silver nanoparticles, and the rod-shaped objects are quercetin. Compared with the original polysiloxane, the atomic force microscopy images show that nanosilver and quercetin are successfully loaded on AQS.

[0047] The anti-adhesion property of AQS is mainly due to its excellent hydrophobic properties. After decompressive craniectomy, AQS is placed between the dura mater and the damaged temporalis muscle to form an isolation barrier. In addition, its good hydrophobicity is more conducive to preventing the formation of adhesions between the temporalis muscle, the bone flap and the dura mater, thereby promoting the healing of the temporalis muscle and reducing the occurrence of complications. Figure 5 The hydrophobic angle of AQS is about 108.88, which is better than that of the original polysiloxane material (96.02, Figure 5 B) and tetrafluoroethylene materials (89.41, Figure 5 A), while the decellularized matrix material is hydrophilic and not hydrophobic, and cannot be compared with AQS.

[0048] The broad-spectrum antibacterial properties of AQS are very beneficial for inhibiting bacterial growth on wounds and improving wound healing efficiency. This is mainly because nanosilver kills bacteria by interfering with bacterial reproduction and destroying bacterial structures, and provides a more suitable microenvironment for the repair of the temporalis muscle. In order to evaluate its antibacterial ability, the two most common standard drug-resistant bacteria (Escherichia coli and Staphylococcus aureus) infected in surgical operations were selected. The CON group without material addition was used as a control. Different materials were co-cultured with Escherichia coli or Staphylococcus aureus. At the same bacterial dilution, the growth of colonies on each plate was as follows: Figure 6As shown in the figure (CON represents the control group; ADM represents the acellular matrix; PTFE represents tetrafluoroethylene; AQS represents the silicone nanocomposite), AQS has a very strong bactericidal ability. After quantifying the number of colonies, it was found that the killing rate of AQS against Escherichia coli exceeded 99%, and the killing rate of AQS against Staphylococcus aureus exceeded 90%. At the same time, the commonly used PTFE and ADM on the market do not have the broad-spectrum antibacterial properties of AQS.

[0049] AQS has certain characteristics of slowly releasing nanosilver and drugs, which is of great significance for sustained antibacterial and anti-inflammatory effects and promoting temporal muscle repair for a period of time after decompressive craniectomy. In order to study the release of silver and quercetin, AQS was soaked in phosphate buffered saline (PBS, PH=7.4) at 37°C. The supernatant was collected every other day and supplemented with an equal amount of fresh PBS. The absorbance of the collected supernatant was measured using a microplate reader, and the concentration of quercetin at different time periods was calculated based on the absorbance. At the same time, the supernatant was mixed and dissolved with an equal volume of aqua regia. The mixture was then diluted to a fixed volume with distilled water and analyzed using an inductively coupled plasma optical emission spectrometer (ICP-OES) to determine the concentration of silver. The release results of silver are shown in the figure. Figure 7 As shown in Figure A, the release of silver in AQS increased dramatically from day 1 to day 7, slowed down significantly from day 7, and reached saturation on day 9. The corresponding release results of quercetin are shown in Figure Figure 7 Middle B shows that the release of quercetin gradually increased from day 1 to day 13. Starting from day 13, the release rate slowed down and reached saturation on day 15. The above results show that AQS loaded with silver and quercetin has good sustained-release properties, which can increase the actual efficacy in antibacterial and anti-inflammatory aspects, thereby further promoting the repair of the temporalis muscle after craniectomy.

[0050] The anti-inflammatory and healing-promoting properties of AQS are mainly achieved by quercetin increasing the expression of anti-inflammatory factor-interleukin 10 and pro-healing factor-proliferating cell nuclear antigen PCNA, and reducing the expression of pro-inflammatory factor-interleukin 6. In order to verify the actual performance of AQS, it was applied to the rat craniectomy decompression model, and the relevant ethics were approved by the Ethics Committee of Harbin Medical University. First, the appropriate skull of the rat was removed and the temporalis muscle was separated. In order to be consistent with the actual clinical operation, the appropriate incision was made after the dura mater was exposed, and the dura mater was sutured in parallel. Then the AQS material was taken and placed between the dura mater and the temporalis muscle and bone edge (such as Figure 2 ), the separated temporalis muscle was repositioned and the skin was sutured. The rats were euthanized at 7 and 14 days after surgery, and the temporalis muscle at the modeling site was sliced ​​and the expression levels of interleukin-6, interleukin-10 and PCNA were detected by immunofluorescence (CON: normal control; DC: simple craniectomy model; AQS: craniectomy model + AQS). Figure 8A and B in the figure are the interleukin-6 levels of rats on the 7th and 14th days after modeling. Figure 8 C and D in the middle are the levels of interleukin-10 on the 7th and 14th days after rat modeling. Figure 8 E and F in the middle are the PCNA levels on the 7th and 14th days after rat modeling. These results show that AQS regulates the inflammatory response by downregulating IL-6 and upregulating IL-10 levels, and increases the expression of the pro-healing factor PCNA to create an environment more conducive to temporalis muscle repair, avoiding excessive inflammatory response to hinder the healing process. The above properties are not possessed by commonly used clinical materials (PTFE, ADM).

[0051] The final effect of AQS on the temporalis muscle in the rat craniectomy model is as follows Fig. 9 As shown in the figure, the temporalis muscle tissue of the modeling rats was sliced ​​and Masson staining was performed to observe the collagen-rich area of ​​the temporalis muscle in different experimental groups on the 7th and 14th days after surgery (collagen staining is blue, muscle fiber staining is red, CON: normal control; DC: simple craniectomy model; AQS: craniectomy model + AQS). The results confirmed that AQS showed good results of multiple effects such as anti-adhesion, antibacterial, anti-inflammatory, and healing promotion. On the 7th day after surgery, the collagen matrix area of ​​the craniectomy group (DC) increased compared with the control group (CON), but the effect was significantly worse than that of the AQS group. On the 14th day, the collagen-rich area of ​​the craniectomy group was still expanding, while the muscle of the AQS group basically completed the reconstruction, and the tissue morphology was close to that of the normal control group, indicating that AQS can significantly promote the remodeling and healing process of the temporalis muscle after craniectomy decompression.

[0052] In summary, the siloxane nanocomposite material AQS, when used in decompressive craniectomy, creates a good healing microenvironment for the damaged temporalis muscle by exerting its anti-adhesion, broad-spectrum antibacterial, anti-inflammatory and healing properties, and effectively promotes the repair of the temporalis muscle after decompressive craniectomy. While improving the quality of patient prognosis and reducing the burden on patients' families and society, AQS also fully reduces medical costs, making it easier to apply and promote it on a large scale in clinical practice.

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A use of a siloxane nanocomposite material in the preparation of a drug for repairing the temporalis muscle after craniectomy, characterized in that: The preparation method of the siloxane nanocomposite material comprises: uniformly mixing nanosilver, quercetin and a solvent to obtain a suspension; adding a polysiloxane film into the suspension for stirring reaction to obtain the siloxane nanocomposite material; The mass ratio of the nanosilver to the polysiloxane film is 1:10; the mass volume ratio of the polysiloxane film to the solvent is 0.2 g:30 mL; the amount of quercetin added is 3 mg / mL solvent; the solvent is deionized water; The preparation method of the polysiloxane film is as follows: 10 mmol of bis(3-aminopropyl)-terminated polydimethylsiloxane is dissolved in 10 mL of dry-treated tetrahydrofuran to obtain a bis(3-aminopropyl)-terminated polydimethylsiloxane solution; 4,4'-diphenylmethane diisocyanate and isophorone diisocyanate are dissolved in tetrahydrofuran, and then added dropwise to the bis(3-aminopropyl)-terminated polydimethylsiloxane solution, and stirred for 5 hours under nitrogen and ice-water bath conditions to obtain an APDMS-NCO solution; then 20 mmol of bis(3-aminopropyl)-terminated polydimethylsiloxane is dissolved in 10 mL of tetrahydrofuran. 2-aminophenylboronic acid, after stirring for 5 minutes, a small amount of insoluble matter is removed with a microporous filter membrane, and then the filtered solution is added to the APDMS-NCO solution, and after stirring for 5 hours, an APDMS-MDI-IPDI-B solution is obtained; the APDMS-MDI-IPDI-B solution is distilled under reduced pressure to remove excess tetrahydrofuran, and poured into a Teflon mold, and dried continuously at room temperature for 24 hours to obtain the polysiloxane film; the stoichiometric ratio of the bis(3-aminopropyl)-terminated polydimethylsiloxane, 4,4'-diphenylmethane diisocyanate, isophorone diisocyanate and 2-aminophenylboronic acid is 1:0.6:1.4:

2.

2. The use of the siloxane nanocomposite material according to claim 1 in preparing a drug for repairing the temporalis muscle after craniectomy, characterized in that: The particle size of the nano silver is 100 nm.

3. Use of the siloxane nanocomposite material according to claim 1 in preparing a drug for repairing the temporalis muscle after craniectomy, characterized in that: The parameters of the stirring reaction are: stirring in the dark for 12-24 hours at room temperature and pressure; the stirring speed is 400-500 rpm.

4. The use of the siloxane nanocomposite material according to claim 1 in preparing a drug for repairing the temporalis muscle after craniectomy, characterized in that: After the stirring reaction is completed, the step of drying the obtained product is also included; the drying is air-drying at room temperature away from light for 0.5 to 1 hour.

Citation Information

Patent Citations

  • Silicon rubber / nano-silver-carrying modified montmorillonite nanometer antibacterial composite material and preparation method thereof

    CN108929543A

  • Nanometer-silver antibacterial coating, its preparation and use

    CN1895683A